Analyses of temporal diversity patterns in a stricto sensu Cerrado fragment - Otoni,Thiago José O (Universidad Austral de Chile, Facultad de Ciencias Forestales, 2016)
We performed a forest inventory in a fragment of stricto sensu Cerrado to evaluate alpha and beta temporal diversity among adult and natural regeneration (NR) strata. Fifteen plots of 1,000 m² (20 × 50 m) were set to sample the adult stratum, and each plot divided in sub-plots of 100 m² (2 × 50 m) to sample NR. We registered the qualitative (species) and quantitative (height and diameter) floristic composition. Natural Regeneration stratum was divided into three diameter classes (I, II and III). Moreover, species collected on non-oriented paths were registered. We estimated alpha diversity through Shannon index (H'), Pielou index (J') and "one-step" jackknife estimator. Sørensen (Sø- qualitative) and Czekanowski (SC - quantitative) indexes were used to evaluate beta diversity. In total, 101 species distributed in 71 genera and 36 families were recorded. For the adult and NR strata, H' values were 3.06 and 3.14 nats per individual, and J' 0.75 and 0.71, respectively. Both strata had qualitative similarity. Natural regeneration showed no similarity with adult stratum by Czekanowski index, although this distance tends to decline with the progressive size of each class. The temporal beta diversity is low between these strata; and there is a trend of increasing similarity with the maturity of NR.